Calibration of a laboratory plasma impedance probe - Tejero, Erik M.; Gatling, George; Paliwoda, Matthew C. (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionThis work describes the calibration of a laboratory plasma impedance probe, a diagnostic to accurately measure the plasma density using resonances in the self-impedance spectrum that are introduced when the probe is immersed in a plasma. This paper focuses on calibration techniques that are essential for typical laboratory plasmas with resonant frequencies above 100 MHz, which corresponds to plasma densities above 108 cm-3 and have been used for plasma densities from 105 to 1010 cm-3 that are found in typical laboratory plasmas. MethodsThe approach uses a calibration circuit included in the measurement circuitry, along with careful characterization of the RF paths after the calibration plane to account for the parasitic impedances. The calibration algorithm is derived and an example step-by-step calibration is presented. Calibration procedures are validated with test loads, numerical simulations, and theoretical models.ResultsThe calibration procedure successfully recovered the impedance of a test load with an average error of 1%. Using a full three-port balun model, the vacuum impedance of the dipole was accurately recovered. Plasma density measurements derived from the calibrated impedance spectrum agreed well with Langmuir probe measurements, while uncalibrated spectra resulted in significant overestimation of plasma density. Monte Carlo simulations demonstrated that using six calibration standards in the SOL calibration significantly improved the accuracy of the calibration coefficients and reduced error in the recovered test load impedance.DiscussionThe calibration procedure described in this manuscript provides accurate impedance measurements in laboratory plasmas, enabling reliable extraction of plasma parameters. The importance of accurate calibration is highlighted with high-frequency measurements using balanced dipole antennas as an example. The use of multiple calibration standards and the full three-port balun model significantly improves measurement accuracy.